2018
DOI: 10.3390/met8121033
|View full text |Cite
|
Sign up to set email alerts
|

Application of a area -Approach for Fatigue Assessment of Cast Aluminum Alloys at Elevated Temperature

Abstract: This paper contributes to the effect of elevated temperature on the fatigue strength of common aluminum cast alloys EN AC-46200 and EN AC-45500. The examination covers both static as well as cyclic fatigue investigations to study the damage mechanism of the as-cast and post-heat-treated alloys. The investigated fracture surfaces suggest a change in crack origin at elevated temperature of 150 ∘ C. At room temperature, most fatigue tests reveal shrinkage-based micro pores as their crack initiation, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…As a part of this Special Issue, researchers were invited to submit their innovative research papers aimed at providing a state-of-the-art knowledge on the topic of metal plasticity, creep deformation and fatigue strength of metals operating at high temperatures, with emphasis on both experimental characterization and numerical modeling of material behavior. A total of eleven research papers were published [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Contributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a part of this Special Issue, researchers were invited to submit their innovative research papers aimed at providing a state-of-the-art knowledge on the topic of metal plasticity, creep deformation and fatigue strength of metals operating at high temperatures, with emphasis on both experimental characterization and numerical modeling of material behavior. A total of eleven research papers were published [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Contributionsmentioning
confidence: 99%
“…In the paper by Aigner et al [3] a model based on the √ area concept proposed by Murakami is extended to elevated temperature by introducing an additional exponent.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since a preliminary study in [56] revealed that the area parameter correlates well with the stress field around the inhomogeneity, this parameter is further utilized in this work for the estimation of defect sizes. The defect size measurement methodology invoked in this work is in detail described in [57,58,59]. According to investigations in [60,61], the statistical distribution of defect sizes can be characterized by the limiting extreme value distribution of the Lognormal (LN) distribution, namely the Gumbel or Extreme Value type one distribution (EV) [62,63].…”
Section: Introductionmentioning
confidence: 99%